PERFORMANCE ANALYSIS OF PAMONG PRAJA POLICE UNITS REGARDING INCIDENTAL ADVERTISING IN BANYUWANGI DISTRICT - Helma Anerga Putri; Hary Priyanto; Leni Vitasari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Incidental advertising is quite widespread in Banyuwangi. Its existence has developed into an important and effective communication model for the promotion of goods and services by individual and private business actors. The purpose of this research is to determine, describe and analyze the performance of the Civil Service Police Unit (Satpol PP) regarding the presence of incidental advertising as regulated in the Banyuwangi Regency Government (Pemkab.) policy . Based on the analysis of research findings, Satpol PP plays a role in determining the success of policies regarding incidental advertising in Banyuwangi Regency. Research recommendations focus on the compliance aspects of the Satpol PP apparatus, the smoothness and absence of problems in policy implementation , as well as effective and sustainable performance in supporting the quality of effective and serving government